Perlindungan Hak Moral Komika Atas Materi Pertunjukan Stand-Up Comedy - Saimima, Vianen; Narwadan, Theresia Nolda Agnes; Balik, Agustina (PATTIMURA Law Study Review, 2024)
ABSTRACT: The role of Intellectual Property Rights (IPR) is increasingly crucial in this modern era, where technology and easy access to information demand strong protection for creative works. One important aspect of IPR is copyright, which gives creators control over the reproduction, distribution, and performance of their works. The copyright law (UUHC) provides broad protection for various types of intellectual works, including art, in accordance with Article 40 Paragraph (1). Stand-Up Comedy, as an art form, should also receive appropriate protection. Even though Stand-Up Comedy performance material is not explicitly mentioned in the UUHC regarding protected objects, Stand-Up Comedy performance material should meet the criteria as a protected copyright work because it is the result of the comic's thought process. However, easy access to Stand-Up Comedy material also raises the problem of plagiarism which can harm copyright and moral rights of comics. The research methods used include normative juridical research with statutory and conceptual approaches, as well as the use of various sources of legal materials, namely primary legal materials, secondary legal materials and tertiary legal materials. Techniques for collecting legal materials through library and electronic resource studies, as well as analysis techniques using qualitative methods. Based on this research, even though Stand-Up Comedy performance material has not been explicitly accommodated in the UUHC, comics' moral rights to their work should receive legal protection. Legal protection can be carried out through preventive and repressive approaches. Dispute resolution involves a legal process, with comics having the option to resolve non-litigation through negotiation, mediation, or arbitration, or through litigation with compensation awarded as recognition of the creator's creative honor and dignity.